TECHNOLOGY OF MICROENCAPSULATION OF GRAIN KIDNEY FAT FRACTION AND ITS APPLICATION IN FUNCTIONAL PRODUCTS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
In the food industry, biologically active oils and their fractions are important raw materials for the production of functional products. Grain kernel oil has many biologically active properties, such as reducing cardiovascular diseases, anti-inflammatory effects, and strengthening the immune system. However, these oils are prone to high levels of constant oxidation, which reduces their quality and makes it difficult to properly integrate them into food products.